Ru(dppbsa)-catalyzed hydrodeoxygenation and reductive etherification of ketones and aldehydes. Issue 7 (25th February 2022) - Sun, Rui; Guo, Hong-Yu; Ma, Shuang-Shuang; Wang, Yao-Feng; Yu, Zheng-Kun; Xu, Bao-Hua
Abstract : Methods for the Ru(dppbsa)-catalyzed hydrodeoxygenation and reductive etherification of ketones and aldehydes were developed. Mechanistic studies suggest two paths with respective rate-limiting step to distinct carbonyl substrates. Abstract : Methods for the Ru(dppbsa)-catalyzed hydrodeoxygenation and reductive etherification of ketones and aldehydes were developed. Carbonyl substrates without β-CH functionality follow a hydrogenation–hydrogenolysis path, wherein the hydrogenolysis of the alkanol intermediates is the rate-limiting step. By contrast, a hydrogenation–dehydration–hydrogenation path is followed by carbonyl substrates with β-CH functionality, suffering from rate-limiting sulfonate ligand-assisted reversible H2 cleavage. This hydrodeoxygenation is competitive with reductive etherification when using alkanols as hydrogen surrogates. The chemoselectivity can be adjusted based not only on the bond strengths of O–H and C–H bonds in the alkanols but also on the steric hindrance of the carbonyl substrates. As a result, both hydrodeoxygenation and reductive etherification exhibit excellent aldehyde tolerance, while the reductive etherification of ketones is highly hindered based on this protocol.